Bigger is not always better: egg size influences survival throughout incubation in brown trout (Salmo trutta). Issue 2 (4th December 2012) - Régnier, Thomas; Bolliet, Valérie; Gaudin, Philippe; Labonne, Jacques
Abstract Classical optimality models for the evolution of egg size predict a single optimal investment for females inferior to the optimal investment for offspring because of the egg size–fecundity trade‐off and the assumption that 'bigger is better' for offspring fitness. Such models do not satisfactorily represent observed within‐population variation in egg size. We measured the influence of maternal investment in egg size on offspring survival in brown trout. Individual measures of egg size, metabolism and survival at different temperatures throughout ontogeny were carried out. We then developed a survival model with regard to egg size, incubation temperature and observed metabolic rate. Small eggs were found to survive at higher rates than large eggs, and the egg size–survival relationship was found to differ among females in accordance with average metabolic rate measured at hatching. These results provide insights for the understanding of the evolutionary significance of egg size variations within a population.